(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article is devoted to the issue of self-esteem of primary school age. Particular attention was paid to the study of the role of the features of self-esteem by such specialists of psychological science as I.S. Kohn, M.I. Lisina, A.I. Lipkina, A.M. Kolyshko, V. D. Shadrikov, R. Burns, E. Erickson, K. Rogers. The study of the formation of self-esteem at primary school age was considered by such teachers as M. I. Lukyanova, L.M. Fridman, L.V. Kovinko, E.E. Danilova, E.I. Rogova and others. The article reveals the concept of «self-evaluation», analyzes the significance of this category, outlines its main functions; the internal and external causes of self-esteem of children of primary school age are described.